2002
DOI: 10.1677/joe.0.1730035
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of vasopressin in the rat transgenic for the metallothionein-vasopressin fusion gene

Abstract: Arginine vasopressin (AVP) is a major antidiuretic hormone, the overproduction of which causes diluting hyponatremia in humans and is called the syndrome of inappropriate antidiuresis (SIAD). To study physiological changes resulting from AVP overproduction and to develop an animal model of hyponatremia, the human AVP gene was expressed under the control of the metallothionein promoter in transgenic (Tg) rats. Analyses of AVP immunoreactivity (irAVP) in the tissues revealed that the transgene is expressed mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Details of the preparation of the rat transgenic for the human AVP gene used in this study have been previously reported (15). Rats were maintained under controlled conditions (23.0°C; lights on from 0900 to 2100), and all procedures were performed in accordance with institutional guidelines for animal care at Nagoya University School of Medicine, which conform to the National Institutes of Health animal care guidelines.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the preparation of the rat transgenic for the human AVP gene used in this study have been previously reported (15). Rats were maintained under controlled conditions (23.0°C; lights on from 0900 to 2100), and all procedures were performed in accordance with institutional guidelines for animal care at Nagoya University School of Medicine, which conform to the National Institutes of Health animal care guidelines.…”
Section: Animalsmentioning
confidence: 99%
“…Recently, we (15,25) developed rats transgenic for the fusion gene consisting of the heavy metal-inducible promoter region of the mouse metallothionein I gene and human AVP gene (Tg). Interestingly, the change in water and electrolyte balance was relatively mild despite a markedly elevated plasma AVP level, suggesting that there may be adaptive mechanisms for maintaining water and electrolyte homeostasis against chronic AVP oversecretion from the earliest stage of life.…”
mentioning
confidence: 99%
“…Details of the preparation of the rat transgenic for the human AVP gene used in this study have been described (Nagasaki et al 2002). Rats were maintained under controlled conditions (23 C; lights on 0900-2100 h), and all procedures were performed in accordance with the institutional guidelines for animal care at Nagoya University School of Medicine, which conform with the NIH animal care guidelines.…”
Section: Animalsmentioning
confidence: 99%
“…Recently, we have generated a rat transgenic for the fusion gene consisting of the heavy metal-inducible promoter region of the mouse metallothionein I gene and human AVP gene (Nagasaki et al 2002). We have revealed that in the rat (1) plasma AVP immunoreactivity was remarkably elevated and increased further by administering zinc sulfate, (2) AVP protein was processed correctly and revealed almost equivalent bioactivity with authentic AVP, and (3) the plasma [Na + ] concentration was not different from control rats under basal conditions, while it declined compared with control rats when a liquid diet containing zinc was provided.…”
Section: Introductionmentioning
confidence: 99%
“…M Molecular weight marker (UX174 Hae III digest), P positive control sample for each transgene Transgenic Res (2009) 18:135-141 139 heavy metals (Zn 2? ) to Tg rats to emphasize the MT promoter (Nagasaki et al 2002). Further research is necessary that considers the correlation between the expression of the c-myc gene and the conditioning of the seminiferous tubules for spermatogonial transplantation in the rats.…”
Section: Resultsmentioning
confidence: 99%